Cost-effectiveness of conventional cytology and HPV DNA testing for cervical cancer screening in Colombia Costo-efectividad de la citología y la tamización con pruebas de ADN-VPH para cáncer de cuello uterino en Colombia - Oscar Andrés-Gamboa; Liliana Chicaíza; Mario García-Molina; Jorge Díaz; Mauricio González; Raúl Murillo; Mónica Ballesteros; Ricardo Sánchez (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: To assess cost-effectiveness of conventional cytology and HPV DNA testing for cervical-cancer screening in Colombia. MATERIAL AND METHODS: The National Cancer Institute of Colombia (NCIC) in 2007 developed a Markov model on the natural history of cervical cancer; no screening, conventional cytology, and HPV DNA testing were compared. Only direct costs were used. Outcomes comprise cervical cancer mortality, years of life saved, and lifetime costs. Discounted incremental cost-effectiveness ratios were estimated and sensitivity analyses were conducted for key parameters. RESULTS: Depending on the screening strategy a 69-81% mortality reduction might be expected. The HPV DNA testing every five years is a cost-effective strategy (Incremental Cost-Effectiveness Ratio (ICER): USD$44/YLS) if the cost per test is under USD$31. The effectiveness was sensitive to coverage and primarily to follow-up. CONCLUSIONS: HPV DNA testing is a cost-effective alternative for screening in Colombia. Not only high coverage but high follow-up rates are critical for successful screening programs. OBJETIVO: evaluar el costo-efectividad de la citología convencional y la prueba de ADN-VPH para tamización de cáncer cervical en Colombia. MATERIAL Y MÉTODOS: el Instituto Nacional de Cancerología de Colombia construyó en 2007 un modelo de Markov de historia natural del cáncer cervical. Se comparó "no tamización", citología convencional y prueba de ADN-VPH. Se utilizaron costos directos. Los desenlaces fueron mortalidad, años de vida ganados y costos. Se calcularon razones de costo-efectividad incremental. Se realizaron análisis de sensibilidad para parámetros clave. RESULTADOS: la mortalidad se redujo 69-81% según la estrategia. La tamización con ADN-VPH cada cinco años es costo-efectiva (ICER (Razón de Costo-Efectividad incremental por sus siglas en inglés): 44 dólares por año de vida saludable) si los costos por prueba son menores a 31 dólares. La efectividad fue más sensible al seguimiento que a la cobertura. CONCLUSIONES: La tamización con prueba ADN-VPH es costo-efectiva para Colombia. No solamente altas coberturas, sino también altos porcentajes de seguimiento son críticos para el éxito de la tamización.